2019
DOI: 10.1108/k-08-2018-0450
|View full text |Cite
|
Sign up to set email alerts
|

Does unified theory of acceptance and use of technology (UTAUT) reduce resistance and anxiety of individuals towards a new system?

Abstract: Purpose Technology acceptance is an incremental approach that has developed over the years. Taking technology acceptance or adoption literature into consideration, the paper aims to investigate the mediating role of adoption readiness, constructed on the basis of the unified theory of acceptance and use of technology (UTAUT), on the relationship between user resistance as well as user anxiety and attitude toward using a system. Design/methodology/approach In consideration of previous studies, the public pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 79 publications
1
21
1
1
Order By: Relevance
“…For example, from a psychological perspective, researchers have suggested that individuals’ behaviours are influenced by their perceived control [ 54 56 ]. Moreover, if a person has perceived control over a situation then certain outcomes are achieved that may facilitate information sharing, such as user acceptance of technology [ 57 , 58 ]. This kind of psychological perception of control increases the likelihood of a certain behaviour.…”
Section: Exploratory Stagementioning
confidence: 99%
“…For example, from a psychological perspective, researchers have suggested that individuals’ behaviours are influenced by their perceived control [ 54 56 ]. Moreover, if a person has perceived control over a situation then certain outcomes are achieved that may facilitate information sharing, such as user acceptance of technology [ 57 , 58 ]. This kind of psychological perception of control increases the likelihood of a certain behaviour.…”
Section: Exploratory Stagementioning
confidence: 99%
“…The original designed UTAUT, as proposed by Venkatesh, et al (2003), consists of four major constructs viz -performance expectancy (PE), effort expectancy (EE), social influence (SI) and facilitating conditions (FC). It is believed that if organisations adopt these four main dimensions, they are most likely to develop a positive attitude towards using new technology (Donmez-Turan, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the context of e-commerce, for example, customers with less experience with online shopping technology may also be more concerned about using it for their shopping activities (Çelik, 2011). Past studies have also indicated a negative relationship between anxiety and the adoption of a new technology, including in the use of mobile payment technology (Bailey et al, 2017;Donmez-Turan, 2019). Based on these premises, the following hypothesis is formulated as follows.…”
Section: Literature Reviewmentioning
confidence: 99%